P-105 The Effect of Vedolizumab on Extraintestinal Manifestations in Patients with Crohn's Disease in GEMINI 2. (March 2016) - Rubin, David; Feagan, Brian; Dryden, Gerald; Melmed, Gil; Lasch, Karen; Abhyankar, Brihad; Xu, Jing; James, Alexandra; Thiny, Michelle
Abstract : Background: Vedolizumab (VDZ) is a gut-selective α4 β7 integrin antagonist with demonstrated efficacy and safety in patients with moderately to severely active Crohn's disease (CD). 1 In post hoc analyses of data from the double-blind (DB) placebo (PBO)-controlled GEMINI 2 study (NCT00783692), we investigated the effect of VDZ on extraintestinal manifestations (EIMs) in the subpopulation of patients who had EIMs at baseline. Methods: Patients received DB PBO, DB VDZ, or open-label VDZ induction. At week 6, VDZ responders were re-randomized to DB PBO (VDZ/PBO) or VDZ every 8 weeks (Q8W) or every 4 weeks (Q4W) for the 46-week maintenance phase. VDZ nonresponders continued on VDZ Q4W and patients who received PBO continued on PBO (PBO/PBO). EIMs were evaluated post hoc from the CD Activity Index (CDAI) complications component. Patients with EIMs were defined as those with (1) any CDAI complication, (2) CDAI complications excluding anal disease-related complications (ie, arthritis/arthralgia, iritis/uveitis, erythema nodosum, pyoderma gangrenosum, aphthous stomatitis, or fever >37.8°C during the past week), (3) any anal disease-related complication (abscess, anal fissure, anal fistula, or other fistula), and (4) arthritis/arthralgia. Kaplan-Meier (KM) estimates for the time to resolution of EIMs were evaluated in patients with baseline EIMs from the PBO/PBO population and all patients receiving VDZ during maintenance (ie, week 6 responders and nonresponders combined). Resolution of EIMs was defined as absence of CDAI complications at each post-baseline study visit until week 52; patients who discontinued the study were counted as not resolved. Hazard ratios (HRs) were calculated over 52 weeks. Results: In total, 494 combined VDZ and 107 PBO/PBO patients had EIM(s) at baseline. KM estimates for resolution of any EIM with VDZ were 13% at week 26 and 32% at week 52 (versus 4% and 23% with PBO, respectively); the HR was 1.4 (95% CI, 0.7–2.79). When excluding anal disease-related complications, KM estimates with VDZ were 18% at week 26 and 43% at week 52 (versus 6% and 23% with PBO, respectively); the HR was 1.87 (95% CI, 0.96–3.64). For resolution of anal disease-related complications, KM estimates with VDZ were 10% at week 26 and 22% at week 52 (versus 6% and 25% with PBO, respectively); the HR was 0.8 (95% CI, 0.18–3.49). KM estimates for resolution of arthritis/arthralgia with VDZ were 19% at week 26 and 42% at week 52 (versus 7% and 26% with PBO, respectively); the HR was 1.84 (95% CI, 0.91–3.71). Conclusions: This post hoc analysis did not show statistically significant benefit of vedolizumab over placebo for the treatment of EIMs in CD. However, within the limitations of the data collection and the fact that the study was not powered to assess EIMs, there was a trend toward benefit. Further study is needed regarding which patients may benefit.